Comprehensive assessment of invalid and indeterminate results in Truenat MTB-RIF testing across sites under the national TB elimination program of India - Gopalaswamy, Radha; Kumar, Nishant; Vashistha, Himanshu; Rajendran, Priya; Kayesth, Jyoti; Peravali, Carel Joseph; Kashyap, Satabdi; Ghosh, Shreeparna; Yumo, Habakkuk; Moore, Moe; Anand, Sridhar; Ramachandran, Ranjani; et al. (Frontiers in Public Health, 2023)
Introduction: Truenat MTB-RIF assay (Truenat), a nucleic acid amplification test (NAAT), is a real-time Polymerase Chain Reaction (RT-PCR) chip-based assay that can detect Mycobacterium tuberculosis (Mtb) and Rifampicin (RIF) drug resistance using portable, battery-operated devices. The National TB Elimination Program (NTEP), India introduced this novel tool at the district and sub-district level in 2020. This study aimed to assess the level and causes of inconclusive results (invalid, errors and indeterminate) in MTB and RIF testing at NTEP sites and the root causes of the same in the programmatic setting. Methods: Truenat testing data for April to June 2021 from 1690 functional Truenat sites in NTEP was analyzed to assess the MTB invalid/errors and RIF indeterminate/error rates. Following this analysis, twelve Truenat sites were selected considering the site performance in Truenat testing, diverse climatic conditions, and geographical terrains. These sites were visited to assess the root causes of the high and low rates of inconclusive results using a structured checklist. Results: A total of 327,649 Truenat tests performed for MTB and RIF testing were analyzed. The rate of MTB invalid was 5.2% [95% confidence interval (CI): 5.11-5.26; n=16,998] and errors were 2.5% (95%CI: 2.46-2.57; n=8,240) in Truenat MTB chip, whereas for Mtb positive samples tested (n=40,926) by Truenat RIF chip for RIF resistance detection, the indeterminate rate was 15.3% (95%CI: 14.97-15.67; n=6,267) and errors were 1.6% (95%CI: 1.53-1.78; n=675). There was a 40.1% retesting gap among Mtb and 78.2% among RR inconclusive results. Among the inconclusive results retested, 27.9% (95%CI: 27.23-28.66; n=4,222) were Mtb positive, and 9.2% (95%CI: 7.84-10.76; n=139) were detected with RR. Conclusion: The main causes affecting Truenat testing performance include suboptimal adherence to standard operating procedures (SOPs), inadequate training, improper storage of testing kits, inadequate sputum quality, lack of quality control, and delays in the rectification of machine issues. Root cause analysis identified that strengthening training, external quality control and supervision could improve inconclusive results. Ensuring hands-on training of technicians for Truenat testing and retesting of samples with inconclusive results are major recommendations while planning for Truenat scale-up.